Hubungan Self Compassion dan Kebersyukuran terhadap Burnout pada Guru Sekolah Dasar - Enny Kusrini; Lukman; Dian Novita Siswanti (Universitas Muhammadiyah Magelang, 2026)
This research is motivated by the increasing professional demands of elementary school teachers that have the potential to cause psychological stress and the risk of burnout. This study aims to analyze the relationship between self-compassion and gratitude and burnout among elementary school teachers in Makassar City. This study used a quantitative approach with a correlational design, involving 300 teachers as respondents selected through a purposive sampling technique. The instruments used included the Maslach Burnout Inventory–Educators Survey (MBI-ES), the Self-Compassion Scale (SCS), and the Gratitude Questionnaire (GQ-6). Data analysis was conducted using Pearson correlation tests and multiple linear regression. The results showed that respondents' burnout levels tended to be low, while self-compassion and gratitude were in the moderate to high categories. Partial tests showed that self-compassion had a negative and significant relationship with burnout (β = -1.019; p < 0.001), as did gratitude (β = -0.861; p < 0.001). Simultaneous tests showed that self-compassion and gratitude were significantly related to burnout (R = 0.717; R² = 0.514; p < 0.001), meaning that both variables were able to explain 51.4% of the variation in burnout. These findings indicate that self-compassion and gratitude act as protective factors in reducing burnout in teachers. The implications of this study emphasize the importance of developing positive psychology-based interventions, such as self-compassion training and gratitude enhancement programs, as preventive strategies to maintain teacher mental health and improve the quality of learning in elementary schools.